Islamic Prayer, Spirituality and Productivity: An Exploratory Conceptual Analysis - Al Haq, M Ashraf; Abd. Wahab, Norazlina; Abd Ghani, Hj Abdullah; Ahmad, Nor Hayati (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2016)
Prayer plays a noteworthy role in Muslims daily lives. Quran and Sunnah testify that regular prayers can boost one’s health, can remove the level of stress, and may make one more productive and vigour. Such findings also noticed by medical and psychological experts, and likewise many contemporary research have shown wide-ranging outcomes in terms of improved wellbeing when prayer is done with sincere devotion. Nevertheless what is lacking is that the policy makers in the Islamic world need to initiate whether there exist any linkages between prayer and productivity, which needs to be appreciated more by them, as well as by Islamic economists and social scientists, Islamic business professionals and Islamic jurists, and then through a concerted effort and dynamic fact finding mission and verification to ascertain the Qur’anic beliefs in our daily lives. This studies using descriptive analysis to explain the linkage between the Islamic prayer and productivityDOI: 10.15408/aiq.v8i2.3160